2018
DOI: 10.1111/nph.15502
|View full text |Cite
|
Sign up to set email alerts
|

A research agenda for seed‐trait functional ecology

Abstract: Summary Trait‐based approaches have improved our understanding of plant evolution, community assembly and ecosystem functioning. A major challenge for the upcoming decades is to understand the functions and evolution of early life‐history traits, across levels of organization and ecological strategies. Although a variety of seed traits are critical for dispersal, persistence, germination timing and seedling establishment, only seed mass has been considered systematically. Here we suggest broadening the range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
251
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 272 publications
(283 citation statements)
references
References 124 publications
(159 reference statements)
6
251
0
1
Order By: Relevance
“…Seed dispersal traits allow us to better understand how far and in what number seeds disperse to sites optimal for survival, germination and seedling establishment (Saatkamp et al, ). In the present study, we expected high seed production and high seed buoyancy potential among mudflat species to adopt long‐distance dispersal in time and space by water and to facilitate the “escaping” strategy through transportation and deposition in large numbers of seeds in available habitats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seed dispersal traits allow us to better understand how far and in what number seeds disperse to sites optimal for survival, germination and seedling establishment (Saatkamp et al, ). In the present study, we expected high seed production and high seed buoyancy potential among mudflat species to adopt long‐distance dispersal in time and space by water and to facilitate the “escaping” strategy through transportation and deposition in large numbers of seeds in available habitats.…”
Section: Discussionmentioning
confidence: 99%
“…For example, orthodox seeds of Rumex maritimus (one of our study species) survived well under different hydrological (dry, moist and wet) regimes when exhumed from artificial burial after 1.5 years (Abedi, Bartelheimer, & Poschlod, ) and even after 5.5 years (S. S. Phartyal, unpublished data). As to the latter, the ability of mudflat species to persist in seed banks is likely an adaptation for bridging the long periods of temporarily unsuitable (flooded) environmental conditions of their habitat (Poschlod & Rosbakh, ), which helps populations to recover via persistent seed banks when conditions become favourable for germination and seedling establishment (Saatkamp et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While plant scientists may all agree that there are gaps in our knowledge of plants (Meyer et al 2016, Gallagher et al 2019, Saatkamp et al 2019, they are unlikely to know where the most gaping holes occur (as found in systematic surveys of botanical trait knowledge; FitzJohn et al 2014). To quantify and understand these gaps, we present an analysis from our recent downloads of global plant databases.…”
Section: Introductionmentioning
confidence: 99%
“…Plant species may be particularly sensitive to environmental filtering at the regeneration stage and this might be more important than other life‐history stages as species could be totally excluded from a habitat due to inappropriate environmental conditions for germination or successful establishment (Grubb, ). However, our knowledge of plant trait ecology is largely focused on few traits concerning aboveground vegetative growth and morphology, and very few studies have assessed the potential role of regeneration traits (Jiménez‐Alfaro, Silveira, Fidelis, Poschlod, & Commander, ; Larson & Funk, ; Poschlod et al., ; Saatkamp et al., ). Regeneration traits have been long acknowledged as relevant to the natural maintenance of biodiversity (Grubb, ), and have been found to be important for both species coexistence and species sorting (Bernard‐Verdier et al., ; Fernández‐Pascual, Pérez‐Arcoiza, Prieto, & Díaz, ; Pierce, Bottinelli, Bassani, Ceriani, & Cerabolini, ).…”
Section: Introductionmentioning
confidence: 99%